Heterointerface engineering of Ni3S2@NiCo-LDH core-shell structure for efficient oxygen evolution reaction under intermittent conditions. (10th December 2022) - Kitiphatpiboon, Nutthaphak; Chen, Meng; Li, Xiumin; Liu, Changlin; Li, Shasha; Wang, Junli; Peng, Shang; Abudula, Abuliti; Guan, Guoqing
Highlights: Self-supported Ni3 S2 @NiCo-LDH nano-grasses electrocatalyst was synthesized on NF by in-situ hydrothermal method coupling with an electrodeposition process. The obtained catalyst had abundant exposed active sites, rich defects and large surface area. The electrode had outstanding OER activity with low overpotential at high current density. The electrode can be stabilized in both continuous and intermittent conditions at high current density. Abstract: Large-scale hydrogen production from water electrolysis using intermittent renewable energy sources such as solar and natural wind systems is currently required to promote the sustainable development goals (SDGs). However, majority of researches focus on water electrolysis under stable operating condition but only a few researches on that under the intermittent condition. Herein, a Ni3 S2 @NiCo-LDH composite electrocatalyst with a core@shell structure was successfully synthesized by heterointerface engineering via an in-situ hydrothermal method coupling with an electrodeposition process. The obtained Ni3 S2 @NiCo-LDH/NF electrode demonstrated superb OER performance with low overpotentials of 305 and 346 mV to deliver current densities of 50 and 100 mA cm −2, respectively. Meanwhile, this electrode remained stable at 100 mA cm −2 in the alkaline solution under both continuous and intermittent conditions without degradation for over 24 h. The remarkable electrocatalytic activity should be attributed to the unique morphology of nano-grasses (core) with nanoflake structure (shell) with a high density of exposed active sites, rich defects and large surface areas. This electrocatalyst design could be applied for the large-scale hydrogen production using electricity generated from intermittent renewable energy. Graphical abstract: Image, graphical abstract